The Roles of Recasts, Task Complexity, and Aptitude in Child Second Language Development. Issue 1 (14th August 2019) - Kourtali, Nektaria‐Efstathia; Révész, Andrea
Abstract : This study investigated the effects of task complexity on child learners' second language (L2) gains, the relationship between aptitude and L2 development, and the extent to which task complexity influences this relationship when recasts are provided. Sixty child EFL learners were assigned to two experimental groups. During the treatment, one group completed simple information transmission tasks, whereas the other group performed complex decision‐making tasks. In response to errors in the use of the present third person singular verb forms, participants received recasts. L2 development was measured through oral production, written production, and elicited imitation tests. Aptitude was assessed through LLAMA D, LLAMA E, and LLAMA F. Less cognitively demanding tasks were more beneficial. Participants' performance on LLAMA E predicted L2 gains measured through elicited imitation, and their LLAMA D scores predicted development measured through the oral and written production tests under complex task conditions. Open Practices: This article has been awarded Open Data and Open Materials badges. The data and materials from this study are publicly accessible via the IRIS digital repository at http://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki . Abstract :